A research on IPO underpricing in China’s A stock Market - Yang, Lin (2015)
IPO underpricing is a common problem in global financial markets, but in China’s stock market it is particularly prominent, which had affected the healthy development of the stock market and the efficient allocation of resources. Therefore, through combination of practice in China’s securities, this paper summarized research findings from foreign literatures. After the analysis of existing research, this paper summarized the transform of IPO issuance system in China's A-share market. Firstly, I choose 879 IPOs between July 2009 and November 2012 as a sample to interpret the affecting factors theoretically. And I consider three hypotheses that may explain the IPO underpricing in China. These are the winner’s curse hypothesis, the ex ante uncertainty hypothesis and the signaling hypothesis. Secondly, multiple linear regression models were used for empirical research on factors affecting IPO underpricing. The existence of higher IPO underpricing in China's stock market is found. In recent years, although there is a declining trend, but IPO underpricing is still at a high level. And China’s IPO underpricing is correlated with turnover, excess buy and asset per share and other factors on capital markets. However, PE ratio, which has influence on IPO underpricing in many mature stock markets, does not have a significant relationship with IPO underpricing in China’s A-share market, while the real root of IPO underpricing in China's stock market lies mainly in China’s imperfect issuance system. Finally, on the basis of the analysis and discussion of the empirical results, I attempt to provide suggestions to the regulatory authorities, the IPO participants and investors.